PREDIKSI CUACA MENGGUNAKAN METODE NEURAL NETWORK - YUNITA YUNITA (LPPM Universitas Bina Sarana Informatika, 2015)
Weather is an important part of people's daily activities. Therefore, many people who need information atmospheric conditions (weather) is more rapid, complete, and accurate. Accurate weather predictions can be used to solve problems arising from the effects of weather such as drought detection, bad weather, crops and production, energy planning industry, aviation, communications and others. Neural Network method is more efficient in computation is fast and capable of handling the data are not stable in the case of typical weather forecast data. For Weather Prediction with synoptic data input is the data. Several experiments were conducted to obtain the optimal architecture and generate accurate predictions. The results showed the artificial neural network method produces an accuracy value of 72.97%.